The Role of Motivation and Job Satisfaction in Enhancing Employee Performance: Systematic Review - Abdelmajid Idris Khalil Mohammed (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This paper seeks to explore the significance of motivation, job satisfaction, and employee performance, with a focus on addressing diverse facets of this issue. The primary challenge at hand pertains to organizations, and institutions, striving to enhance both the productivity and dedication of their workforce. To attain these goals, a multifaceted approach (quantitative and qualitative) was employed, involving comprehensive surveys and interviews conducted among employees in factories, health and educational institutions and companies. The research results demonstrated a robust and positive correlation between motivation and job satisfaction, consistently demonstrating improved performance among highly motivated and contented employees. Key factors influencing this dynamic include equitable compensation, opportunities for skill development, and supportive work environments. Furthermore, it becomes apparent that an all-encompassing approach, which integrates intrinsic and extrinsic motivators, proves more effective in fostering employee engagement. This study underscores the importance of acknowledging the multifaceted nature of employee performance enhancement, offering valuable insights to organizations seeking to cultivate a work environment conducive to maximizing their workforce's potential. The implications of this study are how crucial it is to identify and support job satisfaction and motivational elements in the workplace as major determinants influencing employee performance. Employers stand to gain a great deal by putting tactics into practice that are designed to improve employee motivation, job satisfaction, and work environment. the necessity of customized approaches to accommodate individual differences in motivational demands and work satisfaction preferences as well.